Long-term outcomes of transcatheter atrial septal defect closure: a single-center retrospective study - Honghiranrueng, Lalita; Roymanee, Supaporn; Wongwaitaweewong, Kanjarut; Jarutach, Jirayut; Buntharikpornpun, Rujira (Frontiers in Cardiovascular Medicine, 2024)
Background: Transcatheter atrial septal defect (ASD) closure is the primary approach for treating ASD secundum; however, data on long-term outcomes remain limited. This study aimed to elucidate the prevalence of adverse outcomes following transcatheter ASD closure in a diverse population.Methods: This retrospective cohort study was conducted at the Songklanagarind Hospital and included patients who underwent transcatheter ASD closure between January 2010 and August 2021.The study included 277 patients who completed follow-up for at least 1 year, with varying ages: <25 years (31%), 25-40 years (19%), 40-60 years (34%), and >60 years (16%). The median follow-up duration was 37 months (interquartile range: 20, 61). The overall mortality rate was 1.8%, and no deaths were attributed to device-related complications. Hospitalization due to heart failure occurred in 0.7% of the cases. Most patients improved or stabilized based on the New York Heart Association functional class.Adverse outcomes included new-onset atrial fibrillation (prevalence: 2.7%) and pulmonary hypertension (prevalence: 0.6%). The resolution of pulmonary hypertension varied among age groups, with 100% resolution in patients <25 years. Multivariate analysis identified male sex, overweight, and history of stroke to be significantly associated with adverse outcomes after transcatheter ASD closure.Transcatheter ASD closure was safe and effective, with age not being a limiting factor for success. Male sex, being overweight, and a history of stroke were associated with adverse outcomes. These findings contribute to our understanding of the long-term outcomes following ASD closure.